High-strength stainless steel casting and preparation process thereof
By adding a stainless steel blank body composed of specific elements to stainless steel castings, and preparing abrasion -resistant ceramic coatings on its surface, the problem of corrosion wear and wear of stainless steel castings in a special environment has been solved, and high -intensity and corrosion resistance are improved.
Patent Information
- Application Number
- CN202411565660.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-05
- Publication Date
- 2025-01-24
- Estimated Expiration
- 2044-11-05
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of stainless steel preparation, in particular to a high-strength stainless steel casting and a preparation process thereof. Background Art
[0002] Stainless steel castings are stainless steel products made using a casting process. They have good corrosion resistance, high temperature resistance, strength and toughness, and can be widely used in the automotive, aviation, chemical, medical and other fields. Although stainless steel castings have stronger corrosion resistance than general iron products and can withstand most application scenarios, under special conditions, such as acid, alkali and salt spray environments, stainless steel products will still suffer from corrosion and wear, causing the strength of stainless steel castings to decrease, affecting service life and production safety. Summary of the invention
[0003] The object of the present invention is to provide a high-strength stainless steel casting and a preparation process thereof to solve the problems raised in the prior art.
[0004] To achieve the above object, the present invention provides the following technical solution: a high-strength stainless steel casting having the following technical features: the high-strength stainless steel casting is composed of a stainless steel blank and a wear-resistant ceramic coating coated on the surface of the stainless steel blank; Wherein, by weight percentage, the stainless steel blank consists of 11.4-15.6% chromium, 1.1-2.4% nickel, 1-3% molybdenum, 0.8-1.2% manganese, 0.8-1.2% rhenium, 0.2-0.8% tin, 0.4-0.6% aluminum, 0.05-0.089% cerium, and the balance is iron.
[0005] Furthermore, the wear-resistant ceramic coating has a thickness of 30-120 μm; The wear-resistant ceramic coating consists of a transition coating and an outer wear-resistant coating; Wherein, the thickness ratio of the transition coating to the wear-resistant coating is (1-2):1.
[0006] Furthermore, a method for preparing a high-strength stainless steel casting comprises the following steps: S1. Preparation of stainless steel blank; S11. The raw materials of chromium, nickel, molybdenum, manganese, rhenium, tin, aluminum, cerium and iron were added to a ball mill, and after ball milling and sieving, a metal powder raw material having a particle size of 30-100 μm was obtained; S12. After mixing iron powder, nickel powder, chromium powder and manganese powder in proportion, the mixture is heated to 1550-1620° C., melt-cast into a stainless steel ingot, and then vacuumized. The stainless steel ingot is heated to 1550-1650° C. again, refined for 5-10 minutes, protected by an argon atmosphere, and the remaining raw material powder is added thereto. After melting and mixing, the molten metal is cast into a mold. After cooling to room temperature, the surface of the obtained casting body is polished with 200-800 mesh sandpaper, and then cleaned with anhydrous ethanol to obtain a stainless steel body. S2. Preparation of wear-resistant ceramic coating; S21. The iron and chromium raw materials are placed in a ball mill, ball-milled to 30-80 μm, mixed in a ratio of 7:(2-4), heated to 1580-1600° C., melted, spray-granulated, and sieved to obtain a high chromium alloy powder; S22. The high chromium alloy powder prepared in step S21 is placed in a powder feeding device, and the surface of the stainless steel blank is laser clad during powder feeding to obtain a transition coating; S23. The nano-TiC, nano-WC and high chromium alloy powders were mixed and ball-milled for 60-90 min. The mixed powder was dried and incubated for 12-24 h. The mixed powder was placed in a powder feeding device. When the powder was fed, the surface of the stainless steel blank was laser clad. After the laser cladding was completed, a wear-resistant coating was obtained. S3. In an argon atmosphere, the stainless steel blank with the wear-resistant ceramic coating is heated to 450-550° C., kept at this temperature for 25-40 minutes, and then cooled to room temperature in the furnace to obtain the high-strength stainless steel casting.
[0007] Furthermore, in step S21, the mass ratio of iron to chromium in the high chromium alloy powder is 7:(2-4).
[0008] Furthermore, in step S21, the particle size of the high chromium alloy powder is 2-6 μm.
[0009] Furthermore, in step S22, during laser cladding, the laser spot diameter is 2-4 mm, the laser cladding power is 800-1000 W, and the spot speed is 300-400 mm / min.
[0010] Furthermore, in step S23, in the mixed powder, the mass ratio of the nano-TiC, nano-WC and high-chromium alloy powder is (2-3): (0.5-1): (9-12).
[0011] Furthermore, in step S23, during laser cladding, the laser spot diameter is 2-4 mm, the laser cladding power is 1200-1400 W, and the spot speed is 150-300 mm / min.
[0012] Compared with the prior art, the present invention has the following beneficial effects: In order to improve the strength of the stainless steel casting, the present invention limits the content of each component when preparing the stainless steel casting blank, and increases the amount of chromium added therein, making it the largest metal element in the stainless steel blank except for iron, thereby improving the bonding between the stainless steel blank and the transition coating in the subsequent coating preparation process; In addition, the present invention also adds cerium in the process of preparing the stainless steel blank. The introduction of cerium can effectively improve the stability of the austenite phase in the stainless steel, avoid the brittle phase transformation of the stainless steel blank at high or low temperatures, and thus avoid the occurrence of strength defects in the stainless steel blank during the casting process. On this basis, the present invention further prepares a transition coating and a wear-resistant coating on the surface of the stainless steel blank respectively; in the process of preparing the transition coating, the present invention uses iron and chromium elements to melt to prepare high chromium alloy powder, and uses this as the main material to clad a layer of transition coating on the surface of the stainless steel blank. The iron-chromium ratio in the transition coating is 7: (2-4), which is slightly higher than the iron-chromium ratio in the stainless steel blank, and can effectively alleviate the stress caused by the large component gap between the wear-resistant coating and the stainless steel blank. In addition, when preparing the wear-resistant coating, the present invention still uses high chromium alloy powder as the main material, wherein the higher chromium element can effectively improve the stability of TiC and WC carbides, prevent the decomposition of carbides, and inhibit the graphitization tendency of carbon elements, thereby maintaining the stability and hardness of the coating and improving the corrosion resistance of the material coating. DETAILED DESCRIPTION
[0013] Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in the field without making any creative work shall fall within the scope of protection of the present invention.
[0014] The nano-TiC used in this application is DK-TiC-002 nano-TiC with an average particle size of 200nm; the WC used is DK-WC-002 nano-WC with an average particle size of 400nm; Example 1. A method for preparing a high-strength stainless steel casting, comprising the following steps: S1. Preparation of stainless steel blank; S11. The raw materials of chromium, nickel, molybdenum, manganese, rhenium, tin, aluminum, cerium and iron were added to a ball mill, respectively, and after ball milling and sieving, a metal powder raw material with a particle size of 30-80 μm was obtained; S12. By weight percentage, 80.15% iron powder, 1.8% nickel powder, 13.5% chromium powder and 1.1% manganese powder were mixed in proportion, heated to 1580°C, melted into a stainless steel ingot, and then vacuumed. The stainless steel ingot was heated to 1620°C again, refined for 10 minutes, protected by argon atmosphere, 1.8% molybdenum, 0.8% rhenium, 0.25% tin, 0.5% aluminum, and 0.07% cerium powder were added thereto, melted and mixed evenly, and the molten metal was cast into shape. After cooling to room temperature, the surface of the obtained casting body was polished with 200-800 mesh sandpaper, and then cleaned with anhydrous ethanol to obtain a stainless steel body; S2. Preparation of wear-resistant ceramic coating; S21. The iron and chromium raw materials are placed in a ball mill, ball-milled to 30-80 μm, mixed in a weight ratio of 7:2, heated to 1580°C, melted, spray-granulated, and sieved to obtain a high chromium alloy powder with a particle size of 2-6 μm; S22. The high chromium alloy powder prepared in step S21 is placed in a powder feeding device, and the surface of the stainless steel blank is laser clad during the powder feeding. During the laser cladding, the laser spot diameter is 3 mm, the laser cladding power is 800 W, and the spot speed is 300 mm / min. After the laser cladding is completed, a transition coating with a thickness of 40 μm is obtained; S23. Nano-TiC, nano-WC and high-chromium alloy powder were mixed in a mass ratio of 2:0.5:9, ball-milled for 90 minutes, dried and heat-insulated for 24 hours, and then placed in a powder feeding device. During the powder feeding, the surface of the stainless steel blank was laser clad. The laser spot diameter was 3 mm, the laser cladding power was 1300 W, and the spot speed was 150 mm / min. After the laser cladding was completed, a wear-resistant coating with a thickness of 20 μm was obtained. S3. In an argon atmosphere, the stainless steel blank with the wear-resistant ceramic coating is heated to 530° C., kept at this temperature for 30 minutes, and then cooled to room temperature in the furnace to obtain the high-strength stainless steel casting.
[0015] Example 2. A method for preparing a high-strength stainless steel casting, comprising the following steps: Compared with Example 1, this embodiment increases the amount of chromium added in step S21; S1. Preparation of stainless steel blank; S11. The raw materials of chromium, nickel, molybdenum, manganese, rhenium, tin, aluminum, cerium and iron were added to a ball mill, respectively, and after ball milling and sieving, a metal powder raw material with a particle size of 30-80 μm was obtained; S12. By weight percentage, 80.15% iron powder, 1.8% nickel powder, 13.5% chromium powder and 1.1% manganese powder were mixed in proportion, heated to 1580°C, melted into a stainless steel ingot, and then vacuumed. The stainless steel ingot was heated to 1620°C again, refined for 10 minutes, protected by argon atmosphere, 1.8% molybdenum, 0.8% rhenium, 0.25% tin, 0.5% aluminum, and 0.07% cerium powder were added thereto, melted and mixed evenly, and the molten metal was cast into shape. After cooling to room temperature, the surface of the obtained casting body was polished with 200-800 mesh sandpaper, and then cleaned with anhydrous ethanol to obtain a stainless steel body; S2. Preparation of wear-resistant ceramic coating; S21. The iron and chromium raw materials are placed in a ball mill, ball-milled to 30-80 μm, mixed in a weight ratio of 7:4, heated to 1580° C., melted, spray-granulated, and sieved to obtain a high chromium alloy powder with a particle size of 2-6 μm; S22. The high chromium alloy powder prepared in step S21 is placed in a powder feeding device, and the surface of the stainless steel blank is laser clad during the powder feeding. During the laser cladding, the laser spot diameter is 3 mm, the laser cladding power is 800 W, and the spot speed is 300 mm / min. After the laser cladding is completed, a transition coating with a thickness of 40 μm is obtained; S23. Nano-TiC, nano-WC and high-chromium alloy powder were mixed in a mass ratio of 2:0.5:11, ball-milled for 90 minutes, dried and heat-insulated for 24 hours, and then placed in a powder feeding device. During the powder feeding, the surface of the stainless steel blank was laser clad. The laser spot diameter was 3 mm, the laser cladding power was 1300 W, and the spot speed was 150 mm / min. After the laser cladding was completed, a wear-resistant coating with a thickness of 20 μm was obtained. S3. In an argon atmosphere, the stainless steel blank with the wear-resistant ceramic coating is heated to 530° C., kept at this temperature for 30 minutes, and then cooled to room temperature in the furnace to obtain the high-strength stainless steel casting.
[0016] Example 3. A method for preparing a high-strength stainless steel casting, comprising the following steps: Compared with Example 1, this embodiment increases the laser cladding power in step S22; S1. Preparation of stainless steel blank; S11. The raw materials of chromium, nickel, molybdenum, manganese, rhenium, tin, aluminum, cerium and iron were added to a ball mill, respectively, and after ball milling and sieving, a metal powder raw material with a particle size of 30-80 μm was obtained; S12. By weight percentage, 80.15% iron powder, 1.8% nickel powder, 13.5% chromium powder and 1.1% manganese powder were mixed in proportion, heated to 1580°C, melted into a stainless steel ingot, and then vacuumed. The stainless steel ingot was heated to 1620°C again, refined for 10 minutes, protected by argon atmosphere, 1.8% molybdenum, 0.8% rhenium, 0.25% tin, 0.5% aluminum, and 0.07% cerium powder were added thereto, melted and mixed evenly, and the molten metal was cast into shape. After cooling to room temperature, the surface of the obtained casting body was polished with 200-800 mesh sandpaper, and then cleaned with anhydrous ethanol to obtain a stainless steel body; S2. Preparation of wear-resistant ceramic coating; S21. The iron and chromium raw materials are placed in a ball mill, ball-milled to 30-80 μm, mixed in a weight ratio of 7:2, heated to 1580°C, melted, spray-granulated, and sieved to obtain a high chromium alloy powder with a particle size of 2-6 μm; S22. The high chromium alloy powder prepared in step S21 is placed in a powder feeding device, and the surface of the stainless steel blank is laser clad during the powder feeding. During the laser cladding, the laser spot diameter is 3 mm, the laser cladding power is 1000 W, and the spot speed is 300 mm / min. After the laser cladding is completed, a transition coating with a thickness of 40 μm is obtained; S23. Nano-TiC, nano-WC and high-chromium alloy powder were mixed in a mass ratio of 2:0.5:9, ball-milled for 90 minutes, dried and heat-insulated for 24 hours, and then placed in a powder feeding device. During the powder feeding, the surface of the stainless steel blank was laser clad. The laser spot diameter was 3 mm, the laser cladding power was 1300 W, and the spot speed was 150 mm / min. After the laser cladding was completed, a wear-resistant coating with a thickness of 20 μm was obtained. S3. In an argon atmosphere, the stainless steel blank with the wear-resistant ceramic coating is heated to 530° C., kept at this temperature for 30 minutes, and then cooled to room temperature in the furnace to obtain the high-strength stainless steel casting.
[0017] Example 4. A method for preparing a high-strength stainless steel casting, comprising the following steps: Compared with Example 1, this example increases the amount of nano WC added in step 23; S1. Preparation of stainless steel blank; S11. The raw materials of chromium, nickel, molybdenum, manganese, rhenium, tin, aluminum, cerium and iron were added to a ball mill, respectively, and after ball milling and sieving, a metal powder raw material with a particle size of 30-80 μm was obtained; S12. By weight percentage, 80.15% iron powder, 1.8% nickel powder, 13.5% chromium powder and 1.1% manganese powder were mixed in proportion, heated to 1580°C, melted into a stainless steel ingot, and then vacuumed. The stainless steel ingot was heated to 1620°C again, refined for 10 minutes, protected by argon atmosphere, 1.8% molybdenum, 0.8% rhenium, 0.25% tin, 0.5% aluminum, and 0.07% cerium powder were added thereto, melted and mixed evenly, and the molten metal was cast into shape. After cooling to room temperature, the surface of the obtained casting body was polished with 200-800 mesh sandpaper, and then cleaned with anhydrous ethanol to obtain a stainless steel body; S2. Preparation of wear-resistant ceramic coating; S21. The iron and chromium raw materials are placed in a ball mill, ball-milled to 30-80 μm, mixed in a weight ratio of 7:2, heated to 1580°C, melted, spray-granulated, and sieved to obtain a high chromium alloy powder with a particle size of 2-6 μm; S22. The high chromium alloy powder prepared in step S21 is placed in a powder feeding device, and the surface of the stainless steel blank is laser clad during the powder feeding. During the laser cladding, the laser spot diameter is 3 mm, the laser cladding power is 800 W, and the spot speed is 300 mm / min. After the laser cladding is completed, a transition coating with a thickness of 40 μm is obtained; S23. Nano-TiC, nano-WC and high-chromium alloy powder were mixed in a mass ratio of 2:1:9, ball-milled for 90 minutes, dried and heat-insulated for 24 hours, and then placed in a powder feeding device. During the powder feeding, the surface of the stainless steel blank was laser clad. The laser spot diameter was 3 mm, the laser cladding power was 1300 W, and the spot speed was 150 mm / min. After the laser cladding was completed, a wear-resistant coating with a thickness of 20 μm was obtained. S3. In an argon atmosphere, the stainless steel blank with the wear-resistant ceramic coating is heated to 530° C., kept at this temperature for 30 minutes, and then cooled to room temperature in the furnace to obtain the high-strength stainless steel casting.
[0018] Example 5. A method for preparing a high-strength stainless steel casting, comprising the following steps: Compared with Example 1, the thickness of the transition coating and the wear-resistant coating is increased in this example; S1. Preparation of stainless steel blank; S11. The raw materials of chromium, nickel, molybdenum, manganese, rhenium, tin, aluminum, cerium and iron were added to a ball mill, respectively, and after ball milling and sieving, a metal powder raw material with a particle size of 30-80 μm was obtained; S12. By weight percentage, 80.15% iron powder, 1.8% nickel powder, 13.5% chromium powder and 1.1% manganese powder were mixed in proportion, heated to 1580°C, melted into a stainless steel ingot, and then vacuumed. The stainless steel ingot was heated to 1620°C again, refined for 10 minutes, protected by argon atmosphere, 1.8% molybdenum, 0.8% rhenium, 0.25% tin, 0.5% aluminum, and 0.07% cerium powder were added thereto, melted and mixed evenly, and the molten metal was cast into shape. After cooling to room temperature, the surface of the obtained casting body was polished with 200-800 mesh sandpaper, and then cleaned with anhydrous ethanol to obtain a stainless steel body; S2. Preparation of wear-resistant ceramic coating; S21. The iron and chromium raw materials are placed in a ball mill, ball-milled to 30-80 μm, mixed in a weight ratio of 7:2, heated to 1580°C, melted, spray-granulated, and sieved to obtain a high chromium alloy powder with a particle size of 2-6 μm; S22. The high chromium alloy powder prepared in step S21 is placed in a powder feeding device, and the surface of the stainless steel blank is laser clad during the powder feeding. During the laser cladding, the laser spot diameter is 3 mm, the laser cladding power is 800 W, and the spot speed is 300 mm / min. After the laser cladding is completed, a transition coating with a thickness of 60 μm is obtained; S23. Nano-TiC, WC and high chromium alloy powder were mixed in a mass ratio of 2:0.5:9, ball-milled for 90 minutes, dried and heat-insulated for 24 hours, and then placed in a powder feeding device. During the powder feeding, the surface of the stainless steel blank was laser clad. The laser spot diameter was 3 mm, the laser cladding power was 1300 W, and the spot speed was 150 mm / min. After the laser cladding was completed, a wear-resistant coating with a thickness of 30 μm was obtained. S3. In an argon atmosphere, the stainless steel blank with the wear-resistant ceramic coating is heated to 530° C., kept at this temperature for 30 minutes, and then cooled to room temperature in the furnace to obtain the high-strength stainless steel casting.
[0019] Comparative Example 1. A method for preparing a high-strength stainless steel casting, comprising the following steps: Compared with Example 1, no wear-resistant ceramic coating was prepared in this comparative example; S1. Preparation of high-strength stainless steel castings; S11. The raw materials of chromium, nickel, molybdenum, manganese, rhenium, tin, aluminum, cerium and iron were added to a ball mill, respectively, and after ball milling and sieving, a metal powder raw material with a particle size of 30-80 μm was obtained; S12. According to weight percentage, 80.15% iron powder, 1.8% nickel powder, 13.5% chromium powder and 1.1% manganese powder are mixed in proportion, the temperature is raised to 1580°C, and the stainless steel ingot is melted and cast into a stainless steel ingot. After vacuuming, the stainless steel ingot is heated to 1620°C again, refined for 10 minutes, protected by argon atmosphere, 1.8% molybdenum, 0.8% rhenium, 0.25% tin, 0.5% aluminum, and 0.07% cerium powder are added thereto, and after melting and mixing evenly, the molten metal is cast into shape, and after cooling to room temperature, the surface of the obtained casting is polished with 200-800 mesh sandpaper, and then cleaned with anhydrous ethanol to obtain a high-strength stainless steel casting.
[0020] Comparative Example 2. A method for preparing a high-strength stainless steel casting, comprising the following steps: Compared with Example 1, this comparative example did not perform step S3; S1. Preparation of stainless steel blank; S11. The raw materials of chromium, nickel, molybdenum, manganese, rhenium, tin, aluminum, cerium and iron were added to a ball mill, respectively, and after ball milling and sieving, a metal powder raw material with a particle size of 30-80 μm was obtained; S12. By weight percentage, 80.15% iron powder, 1.8% nickel powder, 13.5% chromium powder and 1.1% manganese powder were mixed in proportion, heated to 1580°C, melted into a stainless steel ingot, and then vacuumed. The stainless steel ingot was heated to 1620°C again, refined for 10 minutes, protected by argon atmosphere, 1.8% molybdenum, 0.8% rhenium, 0.25% tin, 0.5% aluminum, and 0.07% cerium powder were added thereto, melted and mixed evenly, and the molten metal was cast into shape. After cooling to room temperature, the surface of the obtained casting body was polished with 200-800 mesh sandpaper, and then cleaned with anhydrous ethanol to obtain a stainless steel body; S2. Preparation of wear-resistant ceramic coating; S21. The iron and chromium raw materials are placed in a ball mill, ball-milled to 30-80 μm, mixed in a weight ratio of 7:2, heated to 1580°C, melted, spray-granulated, and sieved to obtain a high chromium alloy powder with a particle size of 2-6 μm; S22. The high chromium alloy powder prepared in step S21 is placed in a powder feeding device, and the surface of the stainless steel blank is laser clad during the powder feeding. During the laser cladding, the laser spot diameter is 3 mm, the laser cladding power is 800 W, and the spot speed is 300 mm / min. After the laser cladding is completed, a transition coating with a thickness of 40 μm is obtained; S23. Nano-TiC, WC and high chromium alloy powder are mixed in a mass ratio of 2:0.5:9, and ball-milled for 90 minutes. The obtained mixed powder is dried and kept warm for 24 hours, and then placed in a powder feeding device. During the powder feeding, the surface of the stainless steel blank is laser clad. The laser spot diameter is 3 mm, the laser cladding power is 1300 W, and the spot speed is 150 mm / min. After the laser cladding is completed, a wear-resistant coating with a thickness of 20 microns is obtained, thereby obtaining the high-strength stainless steel casting.
[0021] Comparative Example 3. A method for preparing a high-strength stainless steel casting, comprising the following steps: Compared with Example 1, no transition coating was prepared in this comparative example; S1. Preparation of stainless steel blank; S11. The raw materials of chromium, nickel, molybdenum, manganese, rhenium, tin, aluminum, cerium and iron were added to a ball mill, respectively, and after ball milling and sieving, a metal powder raw material with a particle size of 30-80 μm was obtained; S12. By weight percentage, 80.15% iron powder, 1.8% nickel powder, 13.5% chromium powder and 1.1% manganese powder were mixed in proportion, heated to 1580°C, melted into a stainless steel ingot, and then vacuumed. The stainless steel ingot was heated to 1620°C again, refined for 10 minutes, protected by argon atmosphere, 1.8% molybdenum, 0.8% rhenium, 0.25% tin, 0.5% aluminum, and 0.07% cerium powder were added thereto, melted and mixed evenly, and the molten metal was cast into shape. After cooling to room temperature, the surface of the obtained casting body was polished with 200-800 mesh sandpaper, and then cleaned with anhydrous ethanol to obtain a stainless steel body; S2. Preparation of wear-resistant ceramic coating; S21. The iron and chromium raw materials are placed in a ball mill, ball-milled to 30-80 μm, mixed in a weight ratio of 7:2, heated to 1580°C, melted, spray-granulated, and sieved to obtain a high chromium alloy powder with a particle size of 2-6 μm; S22. Nano-TiC, WC and high chromium alloy powder were mixed in a mass ratio of 2:0.5:9, ball-milled for 90 minutes, dried and heat-insulated for 24 hours, and then placed in a powder feeding device. During the powder feeding, the surface of the stainless steel blank was laser clad. The laser spot diameter was 3 mm, the laser cladding power was 1300 W, and the spot speed was 150 mm / min. After the laser cladding was completed, a wear-resistant coating with a thickness of 20 μm was obtained. S3. In an argon atmosphere, the stainless steel blank with the wear-resistant ceramic coating is heated to 530° C., kept at this temperature for 30 minutes, and then cooled to room temperature in the furnace to obtain the high-strength stainless steel casting.
[0022] Detection: Hardness test: HSV-50 Vickers hardness was used to test the hardness of the high-strength stainless steel castings prepared in Examples 1-5 and Comparative Examples 1-3; Mechanical property testing: The high-strength stainless steel castings prepared in Examples 1-5 and Comparative Examples 1-3 were prepared into 3×4×20 mm specimens, and a tensile test was performed using a universal electronic testing machine to test the tensile strength and elongation thereof; Corrosion resistance test: The high-strength stainless steel castings prepared in Examples 1-5 and Comparative Examples 1-3 were prepared into 50×50×2 mm specimens, which were placed in an environment with an ambient temperature of 35°C and a relative humidity of 95%. A calcium chloride solution with a concentration of 40%, a temperature of 95±3°C, and a pH value of 6.5 was continuously sprayed on the surface of the specimens at a spray volume of 1.5 mL / (80 cm 2 h) Detect the surface corrosion status and record the corrosion resistance time; The high-strength stainless steel casting samples prepared in Examples 1-5 and Comparative Examples 1-3 were heated to 300°C and kept warm for 30 minutes, then cooled to 20°C and kept warm for 1 hour. After 30 cycles, the corrosion resistance was checked again. The test results are shown in the table below;
[0023] Finally, it should be noted that the above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art can still modify the technical solutions described in the aforementioned embodiments or replace some of the technical features therein by equivalents. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A high-strength stainless steel casting, characterized in that: The high-strength stainless steel casting is composed of a stainless steel blank and a wear-resistant ceramic coating coated on the surface of the stainless steel blank; Wherein, by weight percentage, the stainless steel blank consists of 11.4-15.6% chromium, 1.1-2.4% nickel, 1-3% molybdenum, 0.8-1.2% manganese, 0.8-1.2% rhenium, 0.2-0.8% tin, 0.4-0.6% aluminum, 0.05-0.089% cerium, and the balance is iron.
2. A high-strength stainless steel casting according to claim 1, characterized in that: The wear-resistant ceramic coating has a thickness of 30-120 μm; The wear-resistant ceramic coating consists of a transition coating and an outer wear-resistant coating; Wherein, the thickness ratio of the transition coating to the wear-resistant coating is (1-2):
1.
3. The method for preparing a high-strength stainless steel casting according to any one of claims 1 to 2, characterized in that: The following steps are involved: S1. Preparation of stainless steel blank; S11. The raw materials of chromium, nickel, molybdenum, manganese, rhenium, tin, aluminum, cerium and iron are added to a ball mill respectively, and after ball milling and sieving, a metal powder raw material having a particle size of 30-100 μm is obtained; S12. After mixing iron powder, nickel powder, chromium powder and manganese powder in proportion, the mixture is heated to 1550-1620° C., melt-cast into a stainless steel ingot, and then vacuumized. The stainless steel ingot is heated to 1550-1650° C. again, refined for 5-10 minutes, protected by an argon atmosphere, and the remaining raw material powder is added thereto. After melting and mixing, the molten metal is cast into a mold. After cooling to room temperature, the surface of the obtained casting body is polished with 200-800 mesh sandpaper, and then cleaned with anhydrous ethanol to obtain a stainless steel body. S2. Preparation of wear-resistant ceramic coating; S21. The iron and chromium raw materials are placed in a ball mill, ball-milled to 30-80 μm, mixed in proportion, heated to 1580-1600°C, melted, spray-granulated, and sieved to obtain a high chromium alloy powder; S22. The high chromium alloy powder prepared in step S21 is placed in a powder feeding device, and the surface of the stainless steel blank is laser clad during powder feeding to obtain a transition coating; S23. The nano-TiC, nano-WC and high chromium alloy powders were mixed and ball-milled for 60-90 min. The mixed powder was dried and incubated for 12-24 h. The mixed powder was placed in a powder feeding device. When the powder was fed, the surface of the stainless steel blank was laser clad. After the laser cladding was completed, a wear-resistant coating was obtained. S3. In an argon atmosphere, the stainless steel blank with the wear-resistant ceramic coating is heated to 450-550° C., kept at this temperature for 25-40 minutes, and then cooled to room temperature in the furnace to obtain the high-strength stainless steel casting.
4. The method for preparing a high-strength stainless steel casting according to claim 3, characterized in that: In step S21, the mass ratio of iron to chromium in the high chromium alloy powder is 7:(2-4).
5. The method for preparing a high-strength stainless steel casting according to claim 3, characterized in that: In step S21, the particle size of the high chromium alloy powder is 2-6 μm.
6. The method for preparing a high-strength stainless steel casting according to claim 3, characterized in that: In step S22, during laser cladding, the laser spot diameter is 2-4 mm, the laser cladding power is 800-1000 W, and the spot speed is 300-400 mm / min.
7. The method for preparing a high-strength stainless steel casting according to claim 3, characterized in that: In step S23, in the mixed powder, the mass ratio of the nano-TiC, nano-WC and high-chromium alloy powder is (2-3): (0.5-1): (9-12).
8. The method for preparing a high-strength stainless steel casting according to claim 3, characterized in that: In step S23, during laser cladding, the laser spot diameter is 2-4 mm, the laser cladding power is 1200-1400 W, and the spot speed is 150-300 mm / min.
Citation Information
Patent Citations
Alloy powder, coating for surface laser alloying of nodular cast iron and laser alloying method
CN101942593A
Ferritic stainless steel for biofuel supply system part, and biofuel supply system part
CN105296860A
Gradient material steel rail frog prepared by laser cladding
CN110129674A
Ferrite-based stainless steel sheet having low specific gravity and production method therefor
CN110462084A
Raw materials and manufacturing methods for cold-rolled stainless steel sheets
CN110582589A